2013
DOI: 10.1007/s11154-013-9246-8
|View full text |Cite
|
Sign up to set email alerts
|

Bone and vitamin D metabolism in HIV

Abstract: Human immunodeficiency virus (HIV) infection has progressed to a chronic disease and HIV positive individuals are living longer lives. This has lead to an increase in morbidity and mortality due to secondary issues, one being HIV bone disease. HIV infected pediatric and adult populations have a greater incidence in reduction of BMD as compared to the controls. Osteoporosis has been reported to be present in up to 15 % of HIV positive patients. We are starting to understand the mechanism behind the changes in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
0
9
0
1
Order By: Relevance
“…The pathophysiologic mechanisms of bone disease in HIV infection are complex and not fully understood. In addition to traditional risk factors, individuals with HIV are at increased risk for decreased BMD due to concomitant risk factors such as malnutrition, vitamin D deficiency, hypogonadism, antiretroviral therapies, chronic inflammation, and HIV infection itself (5,1317). …”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiologic mechanisms of bone disease in HIV infection are complex and not fully understood. In addition to traditional risk factors, individuals with HIV are at increased risk for decreased BMD due to concomitant risk factors such as malnutrition, vitamin D deficiency, hypogonadism, antiretroviral therapies, chronic inflammation, and HIV infection itself (5,1317). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the majority of people living with HIV in sub-Saharan Africa are young pre-menopausal women[ 9 ], who generally have a low risk of developing osteoporosis and who are under-represented in published studies. Vitamin D deficiency is a well-established secondary cause of osteoporosis in HIV-infected and HIV-uninfected people ([ 10 ]), and a recent South African study has shown that vitamin D deficiency is linked to poverty and is more common in the HIV-infected South African population[ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the use of neither efavirenz, nor TDF, nor any boosted PI regimen significantly influenced the response to vitamin D supplementation despite the potential interference with bone and vitamin D metabolism [ 17 , 23 26 ]. In the absence of HIV-specific factors that seem to influence the response to vitamin D supplementation, as suggested by the results of our data, general recommendations might also apply for PLWH.…”
Section: Discussionmentioning
confidence: 99%